Effect of The Guided Inquiry Learning Model Assisted by Scientific Worksheets on Student’s Competence - Desman Faeri Harefa; Yurnetti Yurnetti (Department of Physics Universitas Negeri Padang, 2023)
Inventive learning models and student-centered learning tools have not been fully utilized. The guided inquiry learning with scientific worksheets is used to determine the effect of using class physics competency models X MIPA SMA Pertiwi 1 Padang. This research used a quasi-experimental design with a Randomized Control Group Only Design. Samplers were selected using cluster random sampling technique. The data collected is in the form of knowledge, attitudes, and skills competencies. The results showed that the evaluation of the knowledge of the experimental sample was 81.11 and that of the control sample was 64.47. The average value of attitude competence for the experimental class was 90.48 and for the control class was 84.01. As for skills, the average value of the experimental group was 87.32 and that of the control group was 77.72. The calculated t value for the three aspects is greater than the t table value which indicates that the hypothesis is accepted. This proves that the use of guided inquiry learning models assisted by scientific worksheets can affect student competence.